Letrozole-associated controlled ovarian hyperstimulation in breast cancer patients versus conventional controlled ovarian hyperstimulation in infertile patients: assessment of oocyte quality related biomarkers - Goldrat, Oranite (Reprod Biol Endocrinol, 2019)
BACKGROUND: Fertility preservation (FP) protocols in case of breast cancer (BC) include mature oocyte cryopreservation following letrozole associated controlled ovarian hyperstimulation (Let-COH). To date, the impact of Let-COH on the follicular microenvironment has been poorly investigated, although a high androgen/estrogen ratio was previously associated with low oocyte quality. METHODS: In this prospective study, follicular fluid (FF) steroid levels (estradiol, testosterone, progesterone) and cumulus cell (CC) gene expression related to oocyte quality (HAS2, PTGS2, GREM1) were compared between 23 BC patients undergoing Let-COH for FP and 24 infertile patients undergoing conventional COH without letrozole. All patients underwent an antagonist COH cycle, and ovulation was triggered with hCG or GnRHa in both groups. RESULTS: FF estradiol levels were significantly lower while testosterone levels were significantly higher in the study group compared to controls irrespective of the trigger method. However, estradiol levels increased significantly with GnRHa triggering compared to hCG in the study group (median = 194.5 (95.4–438) vs 64.4 (43.8–152.4) ng/ml, respectively, p < 0.001), but not in the control group (median = 335.5 (177.5–466.7) vs 354 (179–511) ng/ml, respectively). After hCG trigger, Cumulus cell (CC) gene expression was lower in the study group compared to the control group, and difference was significant for PTGS2. Conversely, CC gene expression of PTGS2 and GREM1 was significantly higher in the study group compared to controls when ovulation was triggered with GnRHa. CONCLUSIONS: Let-COH triggered with hCG may negatively impact oocyte quality. However, ovulation triggering with GnRHa may improve the oocyte microenvironment and cumulus cell genes expression in Let-COH, suggesting a positive impact on oocyte quality in breast cancer patients. TRIAL REGISTRATION: Clinicaltrials.gov -NCT02661932, registered 25 January 2016, retrospectively registered. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12958-018-0443-x) contains supplementary material, which is available to authorized users.